The Impact of Covid-19 Pandemic Towards Socioeconomic Wellbeing of Rural Community in Malaysia. Issue 1 (1st July 2022) - Yusoff, N S; Rashid, M F; Halim, N A
Abstract: The Covid-19 pandemic has impacted the socio-economic well-being of people either in urban or rural areas. The Covid-19 cases and fatalities that concentrated in major urban areas in Malaysia. However, as the pandemic progressed, the rural community faced health vulnerability due to the Covid-19 pandemic threat. Among the significant impacts of the Covid-19 pandemic are income generation, economic activity work, and health vulnerability, especially the rural community involved in rural economic activities such as agriculture and fishery. Therefore, this paper aims to investigate the impact of the Covid-19 pandemic on the socio-economic well-being of rural communities in Malaysia. The case study selection is in Mersing, Pontian and Batu Pahat involving three villages using GIS mapping. The methodology used is quantitative research through a household survey conducted using 182 heads of households based on the economic and social dimensions. The finding reveals that most of the target group experienced a decline in income generation, economic activity restriction, and education issues. Furthermore, there are also decreasing in the economically active population (age 15-60) in the village. As a result, this study is essential in formulating a post-Covid-19 recovery plan regarding socio-economic well-being impacts and the revival of rural community well-being in Malaysia through Geographic Information Systems (GIS) mapping.